A two-dimensional material device and its preparation method and application

Bi2O2Se nanosheets are transferred to the polyamic acid surface through electrostatic adsorption technology and polyimide is generated, which solves the problems of multiple transfers and sliding in the preparation of two-dimensional material devices, and significantly improves the second harmonic performance and strain transfer efficiency.

CN117930560BActive Publication Date: 2025-05-09WESTLAKE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410123334.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-05-09
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

The prior art has multiple transfer processes when preparing two-dimensional material devices, which increases the risk of pollution. The second harmonic performance of two-dimensional materials needs to be further improved, and sliding is prone to occur between the two-dimensional materials and the substrate, reducing the strain transmission efficiency.

Method used

The Bi2O2Se nanosheets are transferred to the polyamic acid surface by electrostatic adsorption technology, and the polyimide is formed by heating to form composite two-dimensional material devices, avoid relative slippage and improve strain transfer efficiency.

Benefits of technology

The stable adhesion between Bi2O2Se nanosheets and organic thin film polyimide is achieved, the strain transfer efficiency is improved, and the second harmonic performance of two-dimensional materials under strain regulation is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117930560B_ABST
    Figure CN117930560B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of two-dimensional material nonlinear optical devices, and specifically relates to a two-dimensional material device, a preparation method thereof, and an application. The preparation method includes: (1) obtaining a substrate uniformly attached with polyamic acid; (2) transferring Bi2O2Se onto the surface of the polyamic acid and heating to obtain a composite two-dimensional material device of polyimide and Bi2O2Se. The present invention adopts a method for improving the adhesion of polymers to firmly adhere Bi2O2Se nanosheets on an organic polymer substrate, effectively avoiding the problem of relative slippage that may occur when strain is applied to the two-dimensional material, realizing efficient strain transfer, and enabling the two-dimensional material to exhibit efficient second harmonic performance under strain regulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of two-dimensional material nonlinear optical devices, and specifically relates to a two-dimensional material device and a preparation method and application thereof. Background Art

[0002] Currently, mature nonlinear materials are three-dimensional optical crystals, such as LiNbO3, etc. However, such materials are difficult to meet the needs of miniaturization and integration of the next generation of optical devices. Optical second harmonic generation (SHG) is a second-order nonlinear optical phenomenon, that is, the frequency of the outgoing light is twice that of the incident light. Optical second harmonic generation is not only an important means to study the structural symmetry, polarization domain distribution and magnetic order of materials in the scientific research field, but also has broad application prospects, such as laser light sources, optical signal processing, quantum light sources, photon modulation, biomedical imaging, etc. The research on two-dimensional materials with optical second harmonic effect has brought a glimmer of hope for the realization of micro-nano photonic devices.

[0003] Currently commonly used two-dimensional materials include transition metal chalcogenides and NbOI2. Transition metal chalcogenides (TMDCs), as the most representative two-dimensional second-order nonlinear optical materials, are particularly noteworthy. However, this material only exhibits central symmetry breaking characteristics in odd-numbered thin films, and even-numbered layers do not have this characteristic. In addition, due to the strong interlayer coupling effect, its electronic band structure changes significantly with increasing thickness. Therefore, its optical second harmonic intensity does not follow the traditional thickness-square relationship and does not increase with increasing thickness. NbOI2 is the two-dimensional material with the highest second harmonic conversion efficiency known to date. This important discovery was published by Abdelwahab et al. in 2022. Subsequently, in 2023, researchers such as Guo Qiangbing used its sister material NbOCl2 film to construct an ultra-thin quantum light source. However, the stability of this type of material in the air needs to be improved, and long-term exposure will cause the film to degrade from the edge, so it is usually necessary to cover and protect it with a hexagonal boron nitride film. Researchers have tried to use diamond anvil cells to apply hydrostatic pressure to large-sized NbOI2 single crystal materials (not thin films) to adjust their second harmonic characteristics. However, this method is technically difficult and cannot serve practical applications.

[0004] The conventional preparation process of existing two-dimensional material real-time strain control devices includes: using the tape dissociation method to transfer the thin film sample to an organic thin film substrate, and then applying strain to the organic substrate. The strain will be transferred to the thin film sample, thereby regulating its physical properties. In this process, the efficiency of strain transfer is affected by the binding force between the thin film sample and the substrate. If the binding force is too small, the sample and the substrate are prone to relative sliding during the strain process, which greatly reduces the strain transmission efficiency. In order to solve this problem, in 2020, Liu Yuan's team innovatively used a spin coating method to encapsulate the transition metal chalcogenide (MoS2) film in a flexible PVA. This method significantly enhances the interaction between the substrate and the material, avoids relative sliding during the strain process, and thus significantly improves the efficiency of strain transfer. This method effectively regulates the optical band gap of MoS2, but the last step is to encapsulate the thin film sample by spin coating the solution, which may contaminate the surface of the sample and is not conducive to the expansion of the application of the device. In addition, the strain regulation range of the second harmonic intensity of existing two-dimensional nonlinear optical materials is mostly around 2 orders of magnitude, which is far lower than the device performance we expect. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects that the prior art involves multiple transfer processes when preparing two-dimensional material devices, which increases the risk of contaminating the two-dimensional material; the second harmonic performance of the existing two-dimensional materials needs to be further improved; slippage is prone to occur between the two-dimensional material and the substrate, reducing the strain transfer efficiency, etc., thereby providing a two-dimensional material strain device and its preparation method and application.

[0006] To this end, the present invention provides the following technical solutions.

[0007] A first aspect of the present invention provides a method for preparing a two-dimensional material device, comprising:

[0008] (1) obtaining a substrate uniformly attached with polyamic acid;

[0009] (2) Bi2O2Se is transferred to the surface of polyamic acid and heated to obtain a composite two-dimensional material device of polyimide and Bi2O2Se.

[0010] The Bi2O2Se is a nanosheet;

[0011] Preferably, the size of the nanosheet is 10×10 μm 2 -50×50μm 2 ;

[0012] Preferably, the thickness of the nanosheet is 10 nm-40 nm.

[0013] The thickness of the polyimide is 30 μm-60 μm;

[0014] Preferably, the two-dimensional material device comprises at least one Bi2O2Se nanosheet.

[0015] Optionally, the two-dimensional material device may further include a plurality of Bi2O2Se nanosheets, for example, 3, 4, 5, 7, 8, 10, 15, etc., and the number thereof is not specifically limited. The shape of the Bi2O2Se nanosheet may be rectangular, square, etc., and the present invention does not specifically limit this.

[0016] The substrate can be an inorganic material such as glass or silicon dioxide, the substrate has good thermal stability at 280° C., and the surface of the substrate is flat.

[0017] The size of the polyimide can be the same as or different from the substrate, preferably the same. The size of the polyimide can be 50×50 mm 2 , 20×40mm 2 , 100×80mm 2 Etc., determined according to actual needs.

[0018] The preparation method, step (2), and heating satisfy at least one of (1) to (3):

[0019] (1) heating to the heating temperature at a heating rate of 8°C / h-11°C / h;

[0020] (2) The heating temperature is 250° C.-280° C.;

[0021] (3) The heating time is 0.5h-3h.

[0022] The preparation method uses electrostatic adsorption technology to transfer Bi2O2Se to the surface of polyamic acid.

[0023] The preparation method, the step (1) comprises: preparing a solution containing polyamic acid, coating the solution on a substrate, and obtaining a substrate uniformly attached with polyamic acid after the solvent evaporates;

[0024] Preferably, the solvent is volatilized by at least one of vacuum drying and heating.

[0025] The step (1) satisfies at least one of (1)-(2):

[0026] (1) The vacuum drying pressure is not higher than 0.2 atmospheres and the time is not less than 5 hours;

[0027] (2) The heating temperature is 50°C-100°C and the heating time is 4h-6h.

[0028] The second aspect of the present invention provides a two-dimensional material device produced by the above-mentioned preparation method.

[0029] The third aspect of the present invention provides an application of the two-dimensional material device prepared by the above preparation method, wherein the application at least comprises applying strain to the two-dimensional material device;

[0030] Preferably, the strain does not exceed 5%;

[0031] Preferably, the strain is 2.5%-5%.

[0032] When applied, the strain applied to the two-dimensional material device can be any value not exceeding 5%, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., and the present invention does not make any specific limitation on this.

[0033] A fourth aspect of the present invention provides a nonlinear optical device, including a two-dimensional material device produced by the above-mentioned preparation method.

[0034] The technical solution of the present invention has the following advantages:

[0035] 1. A method for preparing a two-dimensional material device provided by the present invention comprises (1) obtaining a substrate uniformly attached with polyamic acid; (2) transferring Bi2O2Se to the surface of the polyamic acid, heating, and obtaining a composite two-dimensional material device of polyimide and Bi2O2Se. The present invention adopts a method for improving the adhesion of polymers to firmly adhere Bi2O2Se nanosheets to an organic polymer substrate, effectively avoiding the problem of relative slippage that may occur when strain is applied to the two-dimensional material, achieving efficient transmission of strain, and enabling the two-dimensional material to exhibit efficient second harmonic performance under strain regulation.

[0036] Specifically, the present invention places Bi2O2Se nanosheets on the surface of polyamic acid before polyimide is generated by polycondensation of polyamic acid. The polyimide generated by polycondensation of polyamic acid can produce strong adhesion with Bi2O2Se nanosheets. This adhesion effect can significantly improve the strain transfer efficiency between the substrate and the two-dimensional material, provide a stable strain to the two-dimensional material, and enable it to be effectively applied to strain regulation research. The present invention uses the centrosymmetric semiconductor Bi2O2Se nanosheets with good stability under air as the core material, and utilizes its ferroelectric phase transition mechanism under strain to successfully construct a two-dimensional material device with high-performance optical second harmonic effect. The method of the present invention can produce a two-dimensional material device with high strain transfer efficiency, the device has an efficient optical second harmonic effect under strain regulation, and there is no relative slip problem between the Bi2O2Se nanosheets and the organic thin film polyimide (PI) in the device.

[0037] When preparing two-dimensional material devices, the method of the present invention reduces the device manufacturing process while ensuring the realization of considerable film strain (not higher than 5%), thereby reducing the negative impact of the process on the film quality. By improving the materials and preparation process, the stability of the material is improved, so that it maintains stable second harmonic performance under strain regulation, which helps to extend the service life of the device and its reliability in practical applications. Compared with the prior art, the device manufacturing method of the present invention is simpler and does not require multiple auxiliary transfers, thus avoiding contamination of the device surface and the impact on the second harmonic performance. By optimizing material processing and preparation technology, this method not only improves the efficiency and stability of strain regulation of two-dimensional materials, but also provides strong support for further construction of high-performance second harmonic devices.

[0038] The two-dimensional material device provided by the present invention can be applied to the fields of laser light source, optical signal processing, quantum light source, photon modulation, biomedical imaging, etc.

[0039] 2. The present invention provides a method for preparing a two-dimensional material device. The present invention uses a brush-based electrostatic adsorption technology to transfer Bi2O2Se nanosheets to the surface of polyamic acid without generating additional polymer residues. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 is a flow chart of preparing a two-dimensional material device according to Example 1 of the present invention;

[0042] Figure 2 is the atomic force microscope characterization result of the two-dimensional material device of Example 1 of the present invention;

[0043] Figure 3 The second harmonic spectrum of the two-dimensional material device of Example 1 of the present invention when the incident light wavelength is 1064nm and the strain is different, and the second harmonic spectrum of NbOI2 when the incident light wavelength is 1064nm and the strain is 0;

[0044] Figure 4 It is the second harmonic intensity of the two-dimensional material device of Example 1 of the present invention at an incident light wavelength of 1064nm and different strains, and the second harmonic intensity of NbOI2 and MoS2 at an incident light wavelength of 1064nm and a strain of 0;

[0045] Figure 5It is the second harmonic intensity of the Bi2O2Se two-dimensional device of comparative example 1 of the present invention under different strains with an incident light wavelength of 1064nm;

[0046] Figure 6 This is a schematic diagram of PI in a screw micrometer when testing the performance of a two-dimensional material device in an experimental example of the present invention. DETAILED DESCRIPTION

[0047] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0048] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0049] Example 1

[0050] This embodiment provides a method for preparing a two-dimensional material device. The preparation process is shown in Figure 1 , including the following steps:

[0051] (1) 1.6 g of a polyamic acid solution (PAA solution) with a mass concentration of 15% was prepared, and the PAA solution was evenly applied on a flat glass surface using a scraper. Under the action of gravity and surface tension, the PAA solution formed a smooth and flat coating.

[0052] The above coating was transferred to a vacuum dish and placed horizontally. The vacuum was evacuated and the pressure was maintained below 0.2 atmospheres for 5 hours to allow the solvent in the PAA solution to evaporate. During this process, it was necessary to ensure that the surface of the coating formed by PAA always remained flat. Then the glass sheet was taken out and placed on a hot plate at 70°C for 5 hours, and then heated to 100°C for 1 hour to further remove the solvent. During this process, the flatness of the coating surface was maintained to obtain a substrate with PAA evenly attached.

[0053] (2) Based on the electrostatic adsorption technology of the brush, the size of 25×10μm 2 , a Bi2O2Se nanosheet with a thickness of 26nm was transferred to the surface of PAA, and placed in an oven. The oven was heated to 250℃ at a heating rate of 11℃ / h to make PAA undergo polycondensation reaction to generate polyimide. The reaction time was 3h, and the temperature was naturally lowered to obtain a composite two-dimensional material device of polyimide and Bi2O2Se. Among them, the size of the polyimide is 50×50mm 2 , thickness is 30μm.

[0054] Figure 2 This is the atomic force microscope characterization result of the two-dimensional material device of this embodiment. It can be seen from the figure that Bi2O2Se is evenly covered on the surface of polyimide and fits well with it. There is no relative slip between the two under strain, which leads to a decrease in strain transfer efficiency. Figure 2 It can also be seen that Bi2O2Se is not trapped in or wrapped by the PI film.

[0055] Example 2

[0056] This embodiment provides a method for preparing a two-dimensional material device, comprising the following steps:

[0057] (1) 1.8 g of a polyamic acid solution (PAA solution) with a mass concentration of 15% was prepared, and the PAA solution was evenly applied on a flat silica surface using a scraper. Under the action of gravity and surface tension, the PAA solution formed a smooth and flat coating.

[0058] The above coating was transferred to a vacuum dish and placed horizontally. The vacuum was evacuated and the pressure was maintained below 0.2 atmospheres for 10 hours to allow the solvent in the PAA solution to evaporate. During this process, it was necessary to ensure that the surface of the coating formed by PAA remained flat at all times. Then the silica wafer was taken out and heated on a hot plate at 50°C for 3 hours, and then heated to 100°C for 1 hour to further remove the solvent. During this process, the flatness of the coating surface was maintained to obtain a substrate with PAA evenly attached.

[0059] (2) Based on the electrostatic adsorption technology of the brush, the size of 20×20μm 2 , a Bi2O2Se nanosheet with a thickness of 20nm was transferred to the surface of PAA, and placed in an oven. The oven was heated to 280℃ at a heating rate of 8℃ / h to make PAA undergo polycondensation reaction to generate polyimide. The reaction time was 0.5h, and the temperature was naturally lowered to obtain a composite two-dimensional material device of polyimide and Bi2O2Se. Among them, the size of the polyimide is 50×50mm 2 , thickness is 50μm.

[0060] Example 3

[0061] This embodiment provides a method for preparing a two-dimensional material device, comprising the following steps:

[0062] (1) 1.8 g of a polyamic acid solution (PAA solution) with a mass concentration of 20% was prepared, and the PAA solution was evenly applied on a flat glass surface using a scraper. Under the action of gravity and surface tension, the PAA solution formed a smooth and flat coating.

[0063] The above coating was transferred to a vacuum dish and placed horizontally. The vacuum was evacuated and the pressure was maintained below 0.2 atmospheres for 8 hours to allow the solvent in the PAA solution to evaporate. During this process, it was necessary to ensure that the surface of the coating formed by PAA always remained flat. Then the glass sheet was taken out and placed on a hot plate at 70°C for 4 hours, and then heated to 100°C for 1 hour to further remove the solvent. During this process, the flatness of the coating surface was maintained to obtain a substrate with PAA evenly attached.

[0064] (2) Based on the electrostatic adsorption technology of the brush, the size of the 2 , thickness 20nm, size 10×25μm 2 , thickness 22nm, size 20×20μm 2 , thickness 18nm, size 20×25μm 2 , thickness 17nm, size 25×25μm 2 , thickness 30nm, size 20×40μm 2 , thickness 15nm, size 30×30μm 2 , thickness 25nm, size 30×40μm 2 , thickness 20nm, size 40×40μm 2 , thickness 15nm, size 50×50μm 2 10 Bi2O2Se nanosheets with a thickness of 10nm were transferred to the surface of PAA, which was placed in an oven and heated to 270℃ at a heating rate of 9℃ / h to make PAA undergo polycondensation reaction to generate polyimide. The reaction time was 2h, and the temperature was naturally lowered to obtain a composite two-dimensional material device of polyimide and Bi2O2Se. The size of the polyimide is 100×80mm 2 , thickness is 30μm.

[0065] Comparative Example 1

[0066] This comparative example provides a method for preparing a two-dimensional material device, comprising the following steps:

[0067] (1) 1.6 g of a polyamic acid solution (PAA solution) with a mass concentration of 15% was prepared, and the PAA solution was evenly applied on a flat glass surface using a scraper. Under the action of gravity and surface tension, the PAA solution formed a smooth and flat coating.

[0068] The above coating was transferred to a vacuum dish and placed horizontally. The vacuum was evacuated and the pressure was maintained below 0.2 atmospheres for 6 hours to allow the solvent in the PAA solution to evaporate. During this process, it was necessary to ensure that the surface of the coating formed by PAA remained flat at all times. Then the glass sheet was taken out and placed on a hot plate at 70°C for 10 hours, and then heated to 100°C for 5 hours to further remove the solvent. During this process, the flatness of the coating surface was maintained to obtain a substrate with PAA evenly attached.

[0069] Then, the substrate was transferred to an oven, and the temperature was raised to 250° C. at a heating rate of 11° C. / h to allow PAA to undergo polycondensation. The reaction time was 3 h, and the temperature was naturally lowered to obtain a polyimide (PI) substrate.

[0070] (2) Use thermal release tape to make a 30×30 μm 2 , a Bi2O2Se nanosheet with a thickness of 26nm was transferred to the polyimide surface to obtain a composite device of polyimide and Bi2O2Se. Among them, the size of the polyimide is 50×50mm 2 , thickness is 30μm.

[0071] Test example

[0072] This test example provides the performance of the two-dimensional material device of Example 1 and Comparative Example 1, as follows:

[0073] Cut the 2D material device PI to a size of 30×9mm 2 , paste the PI to the homemade stretching table, such as Figure 6 As shown, the spiral micrometer on the right side of the stretching table is rotated to apply tensile strain to PI. The specific value of the strain length can be obtained by observing the scale of the micrometer, and the strain changes continuously from 0 to 4%. Then, the stretching table is placed on a commercial second harmonic measurement device (WITec, Alpha300RAS) to measure the relationship between the second harmonic intensity and the PI strain in real time to evaluate the strain regulation performance of the two-dimensional material. Single-layer MoS2 and 28nm NbOI2 are used as comparison groups 1-2, and the relationship between the second harmonic intensity and the strain is tested according to the above method. The experimental results are shown in Figure 3-4 .in, Figure 3 It is the second harmonic peak spectrum of the two-dimensional material device of Example 1 under the conditions of incident light wavelength of 1064nm and different strains (0, 3.1%, 3.4%, 3.8%) and the second harmonic peak spectrum of NbOI2 under the conditions of incident light wavelength of 1064nm and strain of 0; Figure 4 It is the second harmonic intensity of the two-dimensional material device of Example 1 under different strains at an incident light wavelength of 1064nm, and the second harmonic intensity of NbOI2 and MoS2 under an incident light wavelength of 1064nm and a strain of 0. Among them, Figure 4The ordinate of the upper figure is the linear coordinate of the harmonic secondary intensity, and the ordinate of the lower figure is the logarithmic coordinate of the harmonic secondary intensity.

[0074] Figure 3-4 It shows that when the wavelength of the incident light is 1064nm, the optical second harmonic intensity of the 26nm Bi2O2Se and PI composite two-dimensional material device under 3.8% strain is 5 times that of a NbOI2 film of similar thickness and about 10,000 times that of a single-layer MoS2, and is expected to be used as a chip-level quantum light source. The optical second harmonic intensity change of the composite two-dimensional material device of Bi2O2Se and PI of the present invention is very sensitive to strain regulation. Near the critical strain of 2.6%, a strain of 0.2% can change its intensity by 3 orders of magnitude, which has great application prospects in optical switches, signal processing, photon modulation, etc.

[0075] The Bi2O2Se and PI composite two-dimensional material device prepared by the present invention utilizes the ferroelectric phase transition of Bi2O2Se nanosheets under strain, accompanied by the breaking of central inversion symmetry, so that it exhibits a huge optical second harmonic response under strain, and the response rate has extremely high strain adjustability.

[0076] Figure 5 This is the second harmonic intensity of the Bi2O2Se two-dimensional device in Example 1 under different strains and an incident light wavelength of 1064nm. It can be seen from the figure that the optical second harmonic response of the device is almost 0 and does not change with the increase of strain. In addition, the adhesion between the nanosheets prepared in Example 1 and PI is weak, slippage is easy to occur, and the strain transfer efficiency is low. Figure 5 The ordinate of the enlarged graph in is the logarithmic coordinate of the second harmonic intensity.

[0077] In Example 2, the second harmonic intensity of the device is 16140a.u. when the strain is 4.3%, which is 8.0 times that of the unstrained NbOI2 of the same thickness. In Example 3, the second harmonic intensity of the device is 12348a.u. when the strain is 3.6%, which is about 4.7 times that of the NbOI2 of the same thickness. This shows that the two-dimensional material device of the present invention has good second harmonic performance.

[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a two-dimensional material device, characterized in that: include: Step (1): obtaining a substrate uniformly coated with polyamic acid; Step (2): Transfer the Bi2O2Se nanosheets to the surface of polyamic acid and heat them to obtain a composite two-dimensional material device of polyimide and Bi2O2Se.

2. The preparation method according to claim 1, characterized in that: The size of the nanosheet is 10×10 μm 2 -50×50μm 2 .

3. The preparation method according to claim 2, characterized in that: The thickness of the nanosheet is 10nm-40nm.

4. The preparation method according to claim 1, characterized in that: The thickness of the polyimide is 30 μm-60 μm.

5. The preparation method according to claim 1, characterized in that: In the step (2), the temperature is raised to 250°C-280°C at a heating rate of 8°C / h-11°C / h and heated for 0.5h-3h.

6. The preparation method according to claim 1, characterized in that: Bi2O2Se was transferred to the surface of polyamic acid using electrostatic adsorption technology.

7. The preparation method according to claim 1, characterized in that: The step (1) comprises: preparing a solution containing polyamic acid, coating the solution on a substrate, and obtaining a substrate uniformly coated with polyamic acid after the solvent evaporates.

8. The preparation method according to claim 7, characterized in that: The solvent is evaporated by at least one of vacuum drying and heating.

9. The preparation method according to claim 8, characterized in that: The vacuum drying pressure is not higher than 0.2 atmospheres, and the time is not less than 5 hours.

10. The preparation method according to claim 8, characterized in that: The heating temperature is 50°C-100°C, and the heating time is 4h-6h.

11. A two-dimensional material device prepared by the preparation method according to any one of claims 1 to 10.

12. Application of the two-dimensional material device prepared by the preparation method according to any one of claims 1 to 10, characterized in that: The application at least includes applying strain to the two-dimensional material device.

13. The use according to claim 12, characterized in that: The strain does not exceed 5%.

14. The use according to claim 13, characterized in that The strain is 2.5%-5%.

15. A nonlinear optical device, characterized in that: Including the two-dimensional material device as described in claim 11.

Citation Information

Patent Citations

  • Preparation method of heat-resistant film

    CN106496615A

  • Preparation method used for in-situ polymerized graphene hybrid modified polyamide acid resin and product

    CN110396193A